2020
DOI: 10.1089/scd.2020.0080
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Derived from Bone Marrow Mesenchymal Stem Cells as Treatment for Severe COVID-19

Abstract: This prospective nonrandomized open-label cohort study addresses the safety and efficacy of exosomes (ExoFloÔ) derived from allogeneic bone marrow mesenchymal stem cells as treatment for severe COVID-19. During April 2020, ExoFlo was provided to 24 SARS-CoV-2 polymerase chain reaction-positive patients at a single hospital center, all of whom met criteria for severe COVID-19 as well as moderate-to-severe acute respiratory distress syndrome. Patients received a single 15 mL intravenous dose of ExoFlo and were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
492
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 547 publications
(545 citation statements)
references
References 32 publications
9
492
2
5
Order By: Relevance
“…Multiple clinical trials using stem cell therapy to treat the COVID-19 have been registered at www.clinicaltrials.gov. Two published studies showed that ACE2 − MSC and exosomes derived from bone marrow MSC could improve the clinical outcome of COVID-19 patients [4,8]. In accordance with our ndings, the use of exosomes derived from bone marrow MSC could increase the oxygenation index of severe COVID-19 patients which may reduce the need for invasive ventilator and shorten hospital stay [8].…”
Section: Discussionsupporting
confidence: 87%
“…Multiple clinical trials using stem cell therapy to treat the COVID-19 have been registered at www.clinicaltrials.gov. Two published studies showed that ACE2 − MSC and exosomes derived from bone marrow MSC could improve the clinical outcome of COVID-19 patients [4,8]. In accordance with our ndings, the use of exosomes derived from bone marrow MSC could increase the oxygenation index of severe COVID-19 patients which may reduce the need for invasive ventilator and shorten hospital stay [8].…”
Section: Discussionsupporting
confidence: 87%
“…In the study by Sengupta et al, a significant mean reduction of 43% in ferritin level was observed in COVID‐19 patients after treatment with exosomes derived from allogeneic bone marrow mesenchymal stem cells 85 …”
Section: Resultsmentioning
confidence: 95%
“…This exosome-based vaccine is an excellent example demonstrating the possibilities of exosomes as nanotherapeutics. Vaccines are not the only possibility as already clinical trials using exosomes derived from allogeneic bone marrow mesenchymal stem cells (ExoFlo) have begun [ 131 ]. ExoFlo was used to treat 24 patients, testing positive for SARS-CoV-2 via polymerase chain reaction [ 131 ].…”
Section: Role Of Evs In the Pathogenesis Of Viral Infectionsmentioning
confidence: 99%